2016
DOI: 10.4155/fmc-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diphenylpropan-1-Ones as Allosteric Modulators of α7 Nach Receptors with Analgesic and Antioxidant Properties

Abstract: Compound 31 is a novel, potent and selective α7 nAChR PAM, displaying antioxidant and analgesic activities. The 1,3-diphenylpropan-1-one scaffold could be the base toward more advanced type I PAMs for the treatment of nAChR-mediated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 52 publications
4
26
0
Order By: Relevance
“…Furthermore, GTS-21 suppressed cisplatin-mediated glutathione depletion ( Fig 5B ) and ROS formation ( Fig 5C ) in renal epithelial cells. Revealing the antioxidant property of GTS-21 is a novel finding, which corroborates the antioxidant property of other α7nAChR agonists [ 60 62 ]. These observations support improved mitochondrial function with GTS-21 treatment in this model but require additional studies to shed more light into the downstream effectors of GTS-21.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, GTS-21 suppressed cisplatin-mediated glutathione depletion ( Fig 5B ) and ROS formation ( Fig 5C ) in renal epithelial cells. Revealing the antioxidant property of GTS-21 is a novel finding, which corroborates the antioxidant property of other α7nAChR agonists [ 60 62 ]. These observations support improved mitochondrial function with GTS-21 treatment in this model but require additional studies to shed more light into the downstream effectors of GTS-21.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, compound 111 exerted analgesic activity in CFA-injected rats (Balsera et al, 2014). Further work studied the compound 31, which displayed an improved potentiation (≈666%, 10 mM of compound) of a7nAChRs-mediated currents (Criado et al, 2016). In CFA-injected rats, the compound 31 displayed analgesic effects similar to those obtained with PNU-120596 (Criado et al, 2016).…”
Section: -Ht 3 Rsmentioning
confidence: 77%
“…Further work studied the compound 31, which displayed an improved potentiation (≈666%, 10 mM of compound) of a7nAChRs-mediated currents (Criado et al, 2016). In CFA-injected rats, the compound 31 displayed analgesic effects similar to those obtained with PNU-120596 (Criado et al, 2016). However, these chalcone-derivate compounds have low aqueous solubility and short time of action in vivo (Balsera et al, 2018).…”
Section: -Ht 3 Rsmentioning
confidence: 93%
See 1 more Smart Citation
“…A brief in vitro study of the pharmacokinetic (PK) properties of compounds 1-3 ( Figure 1) revealed a quite poor PK profile, limiting their therapeutic potential. 31 These results prompted us to synthesize new analogues to improve the pharmacokinetic properties. In this sense, we have recently described the preparation of peptide pro-drugs of some diphenyl propanones with the aim of increasing the in vivo efficacy of the parent drugs, 2 and 3, endowed with longer-lasting effects than their parent drugs.…”
Section: Introductionmentioning
confidence: 99%